Christian Prayer and Song in a Post-Holocaust Church - Anderson, E. Byron (Studies in Christian-Jewish Relations, 2011)
Because liturgy also is ritual and rite through which patterns of linguistic, homiletic, musical, and embodied practices are repeated over time and by which Christian persons are formed, we must pay close attention to the subtle ways in which the “liturgy of supersessionism” persists in our churches. To this end, this article explores questions about the Christian use of the Tetragrammaton in prayer and song; the distinction, or lack thereof, between Sabbath and Sunday; the relationship between the dating of Easter and Passover; and the ways in which Christian prayer and song portray the relationship between Israel and the Church.